Stochastic interpolation model of the medial superior olive neural circuit - Sanda, Pavel; Marsalek, Petr (Brain research, 2012)
This article presents a stochastic model of binaural hearing in the medial superior olive (MSO) circuit. This model is a variant of the slope encoding models. First, a general framework is developed describing the elementary neural operations realized on spike trains in individual parts of the circuit and how the neurons converging onto the MSO are connected. Random delay, coincidence detection of spikes, divergence and convergence of spike trains are operations implemented by the following modules: spike generator, jitter generator, and coincidence detector. Subsequent processing of spike trains computes the sound azimuth in the circuit. The circuit parameters that influence efficiency of slope encoding are studied. In order to measure the overall circuit performance the concept of an ideal observer is used instead of a detailed model of higher relays in the auditory pathway. This makes it possible to bridge the gap between psychophysical observations in humans and recordings taken of small rodents. Most of the results are obtained through numerical simulations of the model.
Keywords: akustická stimulace; Auditory Pathways; Animals; stochastické procesy; modely neurologické; Stochastic Processes; lidé; nucleus olivaris caudalis; Nerve Net; zvířata; sluchová dráha; Action Potentials; Olivary Nucleus; Acoustic Stimulation; nervová síť; akční potenciály; Models, Neurological; Humans